Carok Mat Hasan: Tinjauan Hadits Riwayat Imam Nasa’i Dan Pasal 340 KUHP - Mudthia Nabila Maulud; Tajul Arifin (JISPENDIORA Jurnal Ilmu Sosial Pendidikan Dan Humaniora, 2024)
This research examines the phenomenon of carok in Madura, exploring the reasons and impacts of this occurrence. The aim is to understand the motives behind the violence and its consequences, as well as the related cultural, legal, and religious implications. The study employs a descriptive analytical approach with data from literature such as books, theses, journals, and articles. Findings indicate that carok is triggered by factors like disputes over women, misunderstandings, land conflicts, religious differences, and criminal acts. Although part of Madura's culture, carok has serious repercussions including death and legal violations. The study highlights the importance of effective conflict prevention and resolution. The conclusion emphasizes that carok is often motivated by various factors and leads to violence and legal infractions, with the cases of Mat Hasan and Wardi as examples. The research underscores the significance of peaceful resolution in addressing the complexities of culture, law, and religion in Indonesia.